A case of severe Plasmodium knowlesi in a splenectomized patient - Boo, Yang Liang; Lim, Hong Tak; Chin, Pek Woon; Lim, Suat Yee; Hoo, Fan Kee (Elsevier, 2016)
Plasmodium knowlesi, a zoonotic malaria, is now considered the fifth species of Plasmodium causing malaria in humans. With its 24-hour erythrocytic stage of development, it has raised concern regarding its high potential in replicating and leading to severe illness. Spleen is an important site for removal of parasitized red blood cells and generating immunity. We reported a case of knowlesi malaria in a non-immune, splenectomized patient. We observed the delay in parasite clearance, high parasitic counts, and severe illness at presentation. A thorough search through literature revealed several case reports on falciparum and vivax malaria in splenectomized patients. However, literature available for knowlesi malaria in splenectomized patient is limited. Further studies need to be carried out to clarify the role of spleen in host defense against human malaria especially P. knowlesi.